2016
DOI: 10.1149/2.0941613jes
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Charge Transport in Solid Oxide Mixed Ionic and Electronic Conductors: Nernst-Planck Theory vs Modified Fick's Law

Abstract: With the assumption that the Fermi level (electrochemical potential of electrons) is uniform across the thickness of a mixed ionic and electronic conducting (MIEC) electrode, the charge-transport model in the electrode domain can be reduced to the modified Fick's first law, which includes a thermodynamic factor A. A transient numerical solution of the Nernst-Planck theory was obtained for a symmetric cell with MIEC electrodes to illustrate the validity of the assumption of a uniform Fermi level. Subsequently, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 38 publications
(101 reference statements)
0
11
0
Order By: Relevance
“…[27] and [69], which is equal to the applied overpotential, given that the LSCF potential is found to be almost gradient-less and the deviation of the vacancies and oxide ions from the equilibrium values is limited. Additionally, it can be demonstrated that the contribution associated to the electron transport is equal to that found by Jin et al [42] when rigorously deriving the potential of MIEC electrodes.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…[27] and [69], which is equal to the applied overpotential, given that the LSCF potential is found to be almost gradient-less and the deviation of the vacancies and oxide ions from the equilibrium values is limited. Additionally, it can be demonstrated that the contribution associated to the electron transport is equal to that found by Jin et al [42] when rigorously deriving the potential of MIEC electrodes.…”
Section: Discussionmentioning
confidence: 62%
“…The concentration of background positive charges, which consists of Sr, La and Fe ions, is constant and homogenous in the whole electrode volume. The same assumption is proposed in the ALS model [28] and later by Jin et al [42] for pure LSCF electrodes, wherein the inert and immobile ions are treated as a unique solvent.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Even though the ionic conductivity contributes a small fraction to the total conductivity of a mixed conductor, it does play a crucial role in the ORR catalysis. The thermodynamic factor is a useful term to gauge the enhancement of ionic conduction by fast moving electron holes in mixed conductors 43 . From the data obtained in Fig.…”
Section: Thermodynamic Factor Amentioning
confidence: 99%
“…In the existing literature, the occurrence of nonideality of mixed conducting materials has been widely reported when the charge carrier concentration comprises a significant percentage of the total lattice sites. 15,16 Concentrated solution theory, with the inclusion of activity coefficient of the transporting ion, has generally been employed to account for the nonideal portions of the thermodynamic properties. This research seeks to understand the nonideality of a solid Li-ion active material using nonequilibrium thermodynamics in a concentrated solution to correlate k and D with the activity coefficient of the solid solution (γ).…”
mentioning
confidence: 99%